Murder Leaves Its Mark : A Hawai'i Mystery - Kneubuhl, Victoria N. (Victoria Nalani) (Book collections on Project MUSE., 2011)
When a weekend of horseback rides and beachcombing at the old Haleiwa Hotel turns deadly, Mina Beckwith and Ned Manusia are on the case. The unlikely pair-she a journalist, he a playwright-find themselves once again on the trail of a killer in 1930s Honolulu, where sugar barons cavort at their beachfront mansions while unrest among the working class grows. Their investigation places them in the midst of hot-headed union organizers and the creme de la creme of Honolulu society as well as the riffraff of the city's backstreets. Familiar characters from Ned and Mina's previous adventure, Murder Casts a Shadow, return to lend a hand in another thoroughly entertaining whodunnit from author and playwright Victoria Kneubuhl. Praise for the first Mina Beckwith and Ned Manusia mystery: "Agatha-Christie-in-the-tropics. ... A tightly plotted novel, crackling dialog, and in Mina and Ned, a pair of intelligent and likable sleuths (think Nick and Nora without the alcoholism and veiled disdain). Murder Casts a Shadow shows the promising beginnings of what one hopes will become a new series."--Honolulu Weekly